Conjunctiva derived mesenchymal stem cell (CJMSCs) as a potential platform for differentiation into corneal epithelial cells on bioengineered electrospun scaffolds. Issue 10 (21st June 2017) - Soleimanifar, Fatemeh; Mortazavi, Yousef; Nadri, Samad; Soleimani, Masoud
Abstract: With the aid of tissue engineering, the capability of nanofibrous scaffolds was examined for corneal epithelial differentiation of Conjunctiva mesenchymal stem cells (CJMSCs) as a new source. This study tried to provide a synthetic corneal sheet which could be applied in corneal regeneration. The hybrid arrangement of fine Silk fibers with the diameter of 93.65 nm and the polyurethane (PU) fibers with an average diameter of 575.5 makes a mat with sufficient mechanical properties and interconnected pores that could accelerate nutrient diffusion. After methanol and plasma treatment, the highest biocompatibility of Silk‐PU hybrid nanofibrous scaffolds based on cell attachment and proliferation were proven using MTT assay. The differentiation morphology of cells was observed by SEM micrographs of cells seeded on the scaffold after 12 days treatment through the differentiation medium. Despite up‐regulation of Cytokeratin (CK)3, CK8, CK12, Desmocollin (DSC)1, and Desmoglein (DSG)1 in the treated PU and silk hybrid nanofibrous scaffolds, the relative expression of CK3, CK8, and CK12 genes were highest among TCP, treated PU and silk nanofibrous scaffolds. Immunocytochemistry (ICC) analysis was used to characterize the protein expression of CK3 in CJ‐MSCs seeded on different groups. Although, For both TCP and hybrid group, CJ‐MSCs were positive for corneal epithelial‐specific marker CK3, ICC data demonstrated that CJ‐MSCs seeded on the hybrid group likewise PU or Silk pure nanofibrous scaffolds, could differentiate into corneal epithelial‐like cells. Finally, it was inferred that the hybrid PU and silk nanofibrous scaffold has the potential for the treatment of corneal epithelium. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2703–2711, 2017.